2013
DOI: 10.1589/jpts.25.403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scapular Stabilization Exercise on Function of Paretic Upper Extremity of Chronic Stroke Patients

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the therapeutic effects of scapular stabilization exercise on function of the upper extremity of individuals with chronic hemiparetic stroke.[Subjects] Eleven chronic hemiparetic stroke patients participated in a scapular stabilization exercise program conducted in the sitting position for 30 min per session, 5 days per week, for 4 weeks. We used 3 clinical assessments: the Manual Function Test, the Berg Balance Scale, and the Modified Barthel Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Findings of this study are consistent with those of previous studies that found scapular stabilizer strengthening exercise improves function in the upper extremity in chronic stroke patients 8 ) . Scapular position improved, as did upper extremity function 20 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Findings of this study are consistent with those of previous studies that found scapular stabilizer strengthening exercise improves function in the upper extremity in chronic stroke patients 8 ) . Scapular position improved, as did upper extremity function 20 ) .…”
Section: Discussionsupporting
confidence: 92%
“…However, limited attention has been given to upper-extremity rehabilitation after stroke, and generally functional recovery of the upper limb and hand is limited compared with that of lower extremities 9 , 10 ) . A scapular stabilization exercise program performed over a 4-week period resulted in improvement of upper limb function in an group of 11 chronic hemiparetic patients 11 ) . Even in patients with acute stroke, passive range of motion exercises can improve the function of upper extremities 12 ) .…”
Section: Introductionmentioning
confidence: 99%